Chronic cadmium exposure induced hepatic cellular stress and inflammation in aged female mice. Issue 3 (29th October 2018) - Zhang, Jun; Wang, Yan; Fu, Lin; Wang, Bo; Ji, Yan‐Li; Wang, Hua; Xu, De‐Xiang
Abstract: Previous studies have revealed that acute cadmium (Cd) exposure led to inflammation in different organs through an oxidative stress mechanism. However, whether chronic Cd exposure induces inflammation in liver and the mechanistic link between inflammation and cell stress remains unclear. In the present study, we investigated the effects of chronic Cd exposure on hepatic cellular stress and inflammatory responses. Female CD1 mice were administrated with CdCl2 (10 and 100 mg/L) in drinking water for 57 weeks. Our results showed that the mRNA levels of Inos and the protein content of HO‐1, markers of oxidative stress, were markedly increased in Cd‐treated mice. In addition, the protein level of GRP78, the chaperone of endoplasmic reticulum (ER) stress, was significantly increased in Cd‐treated mice. The expression of the proteins CHOP and peIF2α, two proteins downstream of ER stress, was also upregulated in the Cd‐100 mg/L and Cd‐10 mg/L group, respectively. Moreover, there were increased inflammatory cells existing in liver after Cd administration. Besides, there was a significant elevation in the mRNA level of Mip‐2, Il‐10 and Il‐12 in the Cd‐100 mg/L group. The mRNA level of Tgf‐β was also upregulated in Cd‐treated mice. Moreover, we also found that the number of Ki67‐positive hepatic cells was increased in the Cd‐10 mg/L group. Hence, our results indicated that chronic Cd exposure induced oxidative stress, ER stress, inflammatory responses and proliferation in the liver of aged female mice. Abstract : The aim of the present study was to explore the effects of chronic Cd exposure on hepatic cellular stress and inflammation in aged female mice. Mice were administrated with CdCl2 (10 mg/L and 100 mg/L) in drinking water for 57 weeks. Our results demonstrated that Cd exposure elevated the mRNA/protein level of genes related to hepatic inflammation, cell stress and increased proliferating hepatic cells in Cd‐10 mg/L group. Collectively, chronic Cd exposure induced hepatic cellular stress, inflammation and proliferation.